2014
DOI: 10.1128/genomea.00948-14
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence and Annotation of Acremonium chrysogenum , Producer of the β-Lactam Antibiotic Cephalosporin C

Abstract: The filamentous fungus Acremonium chrysogenum is the industrial producer of the β-lactam antibiotic cephalosporin C. Here, we present the genome sequence of strain ATCC 11550, which contains genes for 8,901 proteins, 127 tRNAs, and 22 rRNAs. Genome annotation led to the prediction of 42 gene clusters for secondary metabolites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…Recently, the total genomic sequence of A. chrysogenum was published [ 58 ], which will facilitate the study of other differentially expressed proteins identified from comparative proteomics between the HY and WT CPC producers. However, future work will still involve characterizing the function of an ORF-encoded protein and studying the means by which the related metabolic pathway affects CPC biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the total genomic sequence of A. chrysogenum was published [ 58 ], which will facilitate the study of other differentially expressed proteins identified from comparative proteomics between the HY and WT CPC producers. However, future work will still involve characterizing the function of an ORF-encoded protein and studying the means by which the related metabolic pathway affects CPC biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…1 ). In fact, clusters containing homologs of both PKS in the direct vicinity are only found in the genomes of Acremonium chrysogenum ( 10 ), Penicillium chrysogenum ( 11 ), Ustilaginoidea virens (GenBank JHTR00000000.1 ), Chaetomium globosum ( 12 ), Colletotrichum graminicola ( 13 ), and Colletotrichum sublineola ( 14 ). Figure 1 gives a schematic representation of the clusters in these species.…”
Section: Introductionmentioning
confidence: 99%
“…In P. chrysogenum , the genes encoding for the two PKS, SorA and SorB, and the FAD-dependent monooxygenase SorC are part of a gene cluster ( Salo et al, 2016 ), which is also present in a range of not closely related ascomycetes, including T. reesei and Acremonium chrysogenum ( Martinez et al, 2008 ; Terfehr et al, 2014 ; Derntl et al, 2016 ; Figure 2 ). The core set of the gene cluster consists of genes encoding for two PKS, an FAD-dependent monooxygenase, a transporter, and two Gal4-like transcription factors.…”
Section: Introductionmentioning
confidence: 99%